Training in young athletes: Ecological dynamics approach - Coppola, S.; Romano, B.; Albano, D.; Vastola, R. (Journal of Human Sport & Exercise, 2021)
Background: Ecological dynamics theories provides a multidisciplinary analysis of the processes involved in skill acquisition, suggesting that the relevant scale of analysis for the comprehension of the learning process is the constrain athlete-environment interactions. Purpose: The aim of this study is to investigate the experimental experiences of implementation of the ecological dynamics approach in the training of young athletes. Methods: A comprehensive search of three databases of literature (PubMed, EBESCO (Sportdiscuss), Web of Science, BASE, Scopus and SpringerLink) from 2010 through 2020 was undertaken. A standard data extraction template was developed to extract the main details for every eligible study. Results: In this study were included 17 articles, 16 of which were experimental and 1 quasi-experimental. All studies were conducted with a sample composed on average of 32 (M = 31.72) subjects aged between 6 and 21.02 years (mean age 12.2 years). The ecological dynamics approach has been tested in 10 sports. Discussions and conclusions: An area in which it is possible to draw conclusions about the didactic effectiveness in the manipulation of specific constraints is in the training of young tennis players. As for the trial carried out in other sports it is not possible to draw conclusions but only suggestions relating to different didactics variations of the implementation of this pedagogical-didactic methodology. Longitudinal studies, with baseline assessment, training and post-training assessment are needed to improve examine the causal relationship between constraint manipulation, learning and motor performances in different sports.